INOVASI PERTANIAN BERKELANJUTAN MELALUI SOSIALISASI BUDIDAYA ANGGUR DAN PRODUKSI ECO ENZYME BERBASIS LIMBAH RUMAH TANGGA DI DESA BELANTING - Khairuddin, Khairuddin; Nurcewy, Sania; Aslamiah, Saibatul; Febrianti, Rini; Putri, Lisa Karena; Yulida, Khoiro; Arrizkie, Mahrizan; Saputra, M. Rizal Eka; Indriani, Rini; Sani, Ardi Alam; Muzaki, Syafira Putri; Anugerah, Rafi (Jurnal Wicara, 2025)
Kuliah Kerja Nyata Pemberdayaan Masyarakat Desa (KKN-PMD) of the University of Mataram in Belanting Village in 2025 was carried out to address the challenges of limited knowledge regarding grape cultivation and the utilization of household waste as eco-friendly fertilizer. The aim of this program was to improve farmers’ skills in grape cultivation and introduce the technology of producing liquid organic fertilizer based on eco enzyme. The methods included problem identification through observation and interviews, program design, and participatory implementation through socialization, counseling, and field practice. The results indicated an increase in farmers’ knowledge of grape cultivation techniques, including seed selection, land preparation, maintenance, and harvesting. Participants were also motivated to cultivate grapes as an alternative commodity with economic potential for the village. In the eco enzyme activity, the community gained new insights into processing household organic waste into liquid fertilizer, which is more cost-effective and environmentally friendly. High enthusiasm was reflected in active participation in practical demonstrations and discussions on fertilizer application in agriculture. Thus, this program has contributed to promoting sustainable agriculture and strengthening community awareness of natural resource management.